Harnessing the Internet for international exchanges on learning cities: The PIE experience 2011-2013. Issue 2 (1st September 2014) - Kearns, Peter
Abstract The PASCAL International Exchanges (PIE) project was developed to facilitate online exchanges of information and experience between learning cities around the world and, in doing this, to test the potential of the internet to enable such low-cost exchanges. The author provides a personal assessment of the PIE experience over the three years 2011 to 2013, and comments on selected significant themes emerging from PIE during these years.